Simulation comparison between equilibrium and rate-based approach for CO2 removal via promoted K2CO3 with glycine - Faezah, Isa; Haslinda, Zabiri; Noorlisa, Harun; Azmi, Mohd Shariff; Nur Kamarul Syaabah, Ng; Muhammad Afif Asyraf, Afian (EDP Sciences, 2021)
The main limitation of rate-based approach in Aspen Plus is the unavailability of the method under dynamic analysis. Hence, to support the development of the integrated process of natural gas treatment at a higher scale, a comprehensive equilibrium and rate-based simulations of CO2 removal via potassium carbonate promoted with glycine (PCGly) is conducted. The purpose of this study is to observe the efficiency of the equilibrium-based model to represent the CO2 removal system before the dynamic simulation can be developed. The validation is conducted based on published experimental data and the result shows that at steady state, the equilibrium-based method is able to predict the CO2 removal as satisfactorily as the rate-based approach. The error deviation between both methods is 2.11 % and through this study, it is shown that the equilibrium-based method is able to simulate the CO2-PGly system efficiently. Thus, this would enable further investigation of the CO2-PGly system under dynamic simulation using the equilibrium-based method.